Reconstructing the history of Panji performances in Southeast Asia - Vickers, Adrian (Wacana, Journal of the Humanities of Indonesia, 2020)
The circulation of Panji stories throughout Southeast Asia has been studied as a textual phenomenon. These same texts, however, provide evidence of how theatrical forms were important as a source for the dispersal of Panji stories. The textual evidence demonstrates that dance-dramas presenting Panji stories were performed in Majapahit times. These dance-dramas, known as raket are continued in the gambuh of Bali as well as in Javanese topeng. They were also widely known in the Malay world, and were connected to Thai and Cambodian theatrical forms.